Greenland, Arch Glacier at Gregory Valley, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1933)
Fig 280 - Arch Glacier and its moraine blocking Gregory Valley. August, 20, 1933. (XIII). (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 192). New York: American Geographical Society.) Arch Glacier, see Fiord Region of East Greenland, p. 192 Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society